Principles of composite material mechanics - Gibson, Ronald F. (Mechanical engineering (Taylor & Francis), 2012)
"Along with new example problems, homework problems, and references, this third edition covers the many exciting developments in areas such as nanocomposites and multifunctional composites. In addition to new topics, including particulate composites as well as joints in composites, the text features extended coverage of micromechanical modeling, finite element analysis, laminated beam theory, mechanical testing of components, non-standard testing of viscoelastic and dynamic behavior, and analysis of bonded and mechanically fastened joints. It also includes the latest ASTM standards. The author also provides a new appendix on the elements of matrix algebra"--